A8.28 Reconstituted high density lipoprotein (RHDL) modulates TH1 and TH17 immune responses and pro-inflammatory cytokine production in a murine model of rheumatoid arthritis. (31st January 2014) - Tiniakou, I; Zannis, V I; Boumpas, D; Verginis, P; Kardassis, D
Abstract : Background and Objectives: High density lipoprotein (HDL) has a variety of functions which confer protection from cardiovascular and other human diseases. Increased cardiovascular risk is observed in humans with autoimmune disorders such as rheumatoid arthritis (RA), which is associated with either low levels or dysfunctional HDL. Recent evidence suggests a role of HDL in modulating both innate and adaptive immune responses. We sought to investigate the role of rHDL during the development of an autoimmune response in the antigen-induced arthritis (AIA) mouse model. Materials and Methods: C57BL/6 mice were subcutaneously immunised with ovalbumin (OVA) in complete Freund's adjuvant (CFA) and the inguinal lymph nodes (LN) were excised 9 days after the antigenic challenge. The LN cells were cultured in vitro in the presence of varying concentrations of reconstituted HDL (rHDL) in the presence or absence of OVA and OVA-specific immune responses were measured. To assess the effect of HDL on dendritic cell activation and maturation, mouse bone marrow was cultured with GM-CSF to generate dendritic cells (BM-DCs), which were collected, cultured and treated with LPS in the presence or absence of rHDL. Results: Presence of rHDL significantly inhibited the proliferation of OVA-primed LN cells in vitro, in a dose-dependent manner, as indicated by IL-2 measurement. Suppressed proliferation accompanied by reduced levels of IFN-γ and IL-17 in culture supernatants indicating that rHDL modulates the induction of Th1 and Th17 effector cells. Finally, rHDL-treated LPS-stimulated BM-DCs secreted significantly lower amounts of pro-inflammatory cytokines such as IL-6 and IL-8 whereas secretion of TNF-α was not affected. Conclusions: rHDL exerts a direct immunomodulatory function on T cells in vitro by suppressing their proliferation and the induction of Th1 and Th17 effector cells. Furthermore, rHDL modulate the secretion of pro-inflammatory cytokines by DCs. Ongoing work is focused on the delineation of the mechanism involved in the rHDL-mediated suppression of the immune response both in vitro and in vivo. These data identify rHDL as an important player in the homeostatic regulation of the inflammatory response and a potential therapeutic target for chronic inflammatory diseases.